PENGARUH PENGGUNAAN GAS ELPIJI TERHADAP PERFORMA MESIN SEPEDA MOTOR 4 TAK 100 CC - Sri Hartono; Joko Suwignyo; Fahmy Fatra; Toni Setiawan (Journal of Vocational Education and Automotive Technology, 2025)
This study aims to measure the impact of LPG on the performance of a 100 cc 4-stroke motorcycle running on pertalite, including torque, engine power, exhaust emissions, and fuel consumption. This quantitative research uses the true experiment method with descriptive analysis to systematically present the test results. The study shows that the torque produced by LPG is 6.49 Nm at 5000 RPM, which is lower than the torque produced by pertalite, which is 7.27 Nm at the same RPM. The engine power generated by LPG is also lower at 5.06 Hp at 7000 RPM, while the engine power on pertalite is higher at 6.13 Hp at the same RPM. In terms of exhaust emissions, LPG is proven to be more environmentally friendly compared to pertalite. LPG exhaust emissions are lower in all components, such as CO, O2, CO2, HC, Lambda, and AFR. Furthermore, LPG is more efficient in fuel consumption, with efficiency reaching 27.99% to 49.98% better than pertalite. Overall, pertalite is superior in terms of torque and engine power, while LPG is better in terms of exhaust emissions and fuel consumption efficiency.